PENGARUH INTERAKSI PEMBELAJARAN DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS TERPADU DI SMP N 2 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Mona, Sri; Ansofino, Ansofino; Areva, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This study aims to determine the extent of the effect of the interaction of learning and student interest and learning and interaction influences student interest together the results of an integrated social studies students of SMP N 2 Lembah Melintang Kabupaten West Pasaman . This research is descriptive Associative . The population in this study were all students of SMP N 2 Valley Crossing West Pasaman , with a sample of 84 respondents . The sampling technique is simple random sampling . The type of data used , namely primary and secondary data . To determine the effect of the interaction of learning and student interest toward learning outcomes students integrated IPS SMP N 2 Lembah Melintang Kabupaten West Pasaman used the t test and F test.That Describe First Results : Variable Interaction Learning significant and positive impact on learning outcomes Integrated Social eighth grade students of SMP N 2 Lembah Melintang Kabupaten West Pasaman . This is evidenced by the coefficient value of 0.692 and the value of t ( 8.958 ) > t table ( 1.663 ) . That is when the learning interaction is increased by 1 % and keep student interest , then the results of an integrated social studies students of SMP N 2 Lembah Melintang Kabupaten West Pasaman will increase by 0.692 % . Second : Variable student interest and a positive significant effect on the results of an integrated social studies eighth grade students of SMP N 2 Lembah Melintang Kabupaten West Pasaman . This is evidenced by the coefficient value of 0.674 and the value of t ( 9.301 ) > t table ( 1.663 ) . This means that if student interest is increased by 1 % and still learning interaction , the results of an integrated social studies eighth grade students of SMP N 2 Valley Crossing West Pasaman will increase by 0.674 % . Third : Variable interaction of learning and student interest has a significant and positive influence on the results of the integrated IPS Learning Eighth Grade Students of SMP N 2 Valley Crossing West Pasaman the value of F ( 329.126 ) > Ftable ( 3,960 ) and Sig ( 0.000 ) < Alpha ( 0.05 ) . Percentage of interaction variables influence learning and student interest to the integrated IPS Learning Outcomes Eighth Grade Students of SMP N 2 Lembah Melintang Kabupaten West Pasaman that is equal to 89 % , while the remaining 11 % is explained by other causes that are outside the study .Â